The Effect of Corporate Social Responsibility Disclosure of Return Assets Through Sales Growth as Intervening Variable - Yuztiya Asmaranti (Politeknik Negeri Lampung, 2011)
This study aims to analyze the effects of corporate social responsibility disclosure of return on assets (ROA) through sales growth. population Sampling of this study are the firms within industries with high level of environmental pollution (for example: paper and allied products, mining and mining services, metal and allied products, fabricated metal products, electronics and office equipment and chemicals and Allied products). The path analysis model was used to measure the effect of corporate social responsibility disclosure, as an exogenous variable, of return on assets (ROA), as endogenous variable, through sales growth as an intervening variable. Based on this research, it was found that 1) corporate social responsibility disclosure had positive effect on sales growth, 2) corporate social responsibility disclosure and sales growth simultaneously and partially had positive effect on return on assets (ROA). Keywords: corporate social responsibility disclosure, return on assets (ROA), sales growth